Transposable elements and Piwi‑interacting RNAs in hemato‑oncology with a focus on myelodysplastic syndrome (Review) - Merkerova, Michaela Dostalova; Krejcik, Zdenek (International journal of oncology, 2021)
Our current understanding of hematopoietic stem cell differentiation and the abnormalities that lead to leukemogenesis originates from the accumulation of knowledge regarding protein‑coding genes. However, the possible impact of transposable element (TE) mobilization and the expression of P‑element‑induced WImpy testis‑interacting RNAs (piRNAs) on leukemogenesis has been beyond the scope of scientific interest to date. The expression profiles of these molecules and their importance for human health have only been characterized recently due to the rapid progress of high‑throughput sequencing technology development. In the present review, current knowledge on the expression profile and function of TEs and piRNAs was summarized, with specific focus on their reported involvement in leukemogenesis and pathogenesis of myelodysplastic syndrome.
Keywords: RNA, Small Interfering; Animals; Myelodysplastic Syndromes; lidé; myelodysplastické syndromy; zvířata; myelodysplastic syndrome; DNA Transposable Elements; P‑element‑induced WImpy testis‑interacting RNAs; malá interferující RNA; transpozibilní elementy DNA; transposable element; leukemia; Humans